Theoretical Investigation of Optoelectronic and Photophysical Properties in the Carbazole-based Molecules via DFT and TD-DFT Methodology - Sabir, Muhammad Zohaib; Ismaeel, Sania; Ali, Yasir; Kanwal, Aneeqa; Siddiqua, Umme Habibah (My University, 2026)
The growing need for renewable energy resources has brought small-molecule organic solar cells into focus as one of the potential candidates for future generation photovoltaics owing to their easy manufacturing process, flexibility, and lightweight nature. This paper presents the theoretical investigation carried out through density functional theory (DFT) and time-dependent DFT (TDDFT) methods for designing and characterizing a series of five novel donor materials (CA1-CA5) based on carbazole core, thiophene spacer, and various functionalized terminal electron-withdrawing acceptors. Analysis of the results obtained from frontier molecular orbitals suggests that functionalization of the terminal acceptor can modulate the electronic properties, such as the energy level and band gap of these molecules. Remarkably, CA2 and CA1 possess lower band gaps (2.71 eV and 2.81 eV, respectively) than the reference material (3.48 eV) and are therefore expected to have higher charge transfer efficiency. Strong intramolecular charge transfer (ICT) is observed in all molecules using transition density matrix and molecular electrostatic potentials. Additionally, CA1 and CA2 are identified to have high oscillator strength and absorption at the longest wavelength, implying high light-harvesting ability.
Keywords: Carbazole-based core; DFT calculation; Intramolecular charge transfer (ICT); Thiophene spacer; Time-dependent DFT